2010
DOI: 10.3354/meps08778
|View full text |Cite
|
Sign up to set email alerts
|

Predator–prey relationships and foraging ecology of a marine apex predator with a wide temperate distribution

Abstract: The diet of the broadnose sevengill shark Notorynchus cepedianus was investigated over 3 years from 2 coastal locations in south-east Tasmania: the Derwent Estuary and Norfolk Bay. In general, individuals from both locations consumed the same broad dietary categories (sharks, batoids, teleosts and mammals). However, within these categories, species composition differed. Variations in chondrichthyan prey consumed matched estimations of prey abundance: Mustelus antarcticus was the primary prey in Norfolk Bay, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
74
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(77 citation statements)
references
References 52 publications
(65 reference statements)
2
74
0
Order By: Relevance
“…They are seasonally abundant in shallow coastal habitats (Ebert 1989, Lucifora et al 2005, Barnett et al 2010a, where they feed mostly on other elasmobranchs, marine mammals and teleosts (Ebert 1989, 1991, Lucifora et al 2005, Braccini 2008, Barnett et al 2010b. Recently, an intensive 3-yr study on sevengill shark ecology was conducted in 2 coastal habitats of southeast Tasmania, Australia, where information on diet, population structure, habitat use and movement patterns was collected (Barnett et al 2010a(Barnett et al ,b,c, 2011.…”
Section: Abstract: Chondrichthyans · Coastal · Diet · Movement · Stamentioning
confidence: 99%
See 2 more Smart Citations
“…They are seasonally abundant in shallow coastal habitats (Ebert 1989, Lucifora et al 2005, Barnett et al 2010a, where they feed mostly on other elasmobranchs, marine mammals and teleosts (Ebert 1989, 1991, Lucifora et al 2005, Braccini 2008, Barnett et al 2010b. Recently, an intensive 3-yr study on sevengill shark ecology was conducted in 2 coastal habitats of southeast Tasmania, Australia, where information on diet, population structure, habitat use and movement patterns was collected (Barnett et al 2010a(Barnett et al ,b,c, 2011.…”
Section: Abstract: Chondrichthyans · Coastal · Diet · Movement · Stamentioning
confidence: 99%
“…Preferential or specialist foraging behavior was also suspected in some individuals, but since most (76%) stomachs sampled only contained one or 2 prey items, and because sevengills in general were found to consume a wide range of prey, individual variations in foraging behavior were hard to determine from stomach content data alone (Barnett et al 2010b). Since stable isotope analysis provides longterm diet information, as opposed to the short-term snapshot that is acquired by the analysis of stomach contents, this technique may be more appropriate to investigate intrapopulation differences in diet (Vander Zanden & Rasmussen 2002, Matthews & Mazumder 2004).…”
Section: Abstract: Chondrichthyans · Coastal · Diet · Movement · Stamentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, studies utilizing stomach contents to examine the feeding chronology of large-bodied species almost exclusively focus on neonates and juveniles (e.g. Medved et al 1985, Cortés & Gruber 1990, Bush 2003, Barry et al 2008, Kubodera et al 2007, TorresRojas et al 2010, with the notable exception of Barnett et al (2010) who examined stomachs from all size classes of broadnose sevengill sharks Noto rhynchus cepedianus. Conversely, our method includes all life stages that are susceptible to longline gear.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly important as past studies have shown ontogenetic shifts to occur in the feeding biology of specific sharks (Wetherbee & Cortés 2004), including Atlantic sharpnose (Hoffmayer & Parsons 2003), blacktip (Barry et al 2008), bull (Cliff & Dudley 1991) and sandbar (McElroy et al 2006) sharks. Furthermore, with the exception of Barnett et al (2010) and aspects of Cortés & Gruber (1990), all studies we are aware of that examined the feeding chronology of a shark species utilizing stomach content analyses used lethal methodology. While our method is logistically intensive, analyses of longline time-at-capture data does not require that individuals be sacrificed, thus making this methodology a non-lethal alternative to stomach content analyses.…”
Section: Discussionmentioning
confidence: 99%